Dynamic evaluation of blood flow microcirculation by combined use of the laser Doppler flowmetry and high‐speed videocapillaroscopy methods. Issue 6 (7th February 2019) - Dremin, Viktor; Kozlov, Igor; Volkov, Mikhail; Margaryants, Nikita; Potemkin, Andrey; Zherebtsov, Evgeny; Dunaev, Andrey; Gurov, Igor
Abstract : The dynamic light scattering methods are widely used in biomedical diagnostics involving evaluation of blood flow. However, there exist some difficulties in quantitative interpretation of backscattered light signals from the viewpoint of diagnostic information. This study considers the application of the high‐speed videocapillaroscopy (VCS) method that provides the direct measurement of the red blood cells (RBCs) velocity into a capillary. The VCS signal presents true oscillation nature of backscattered light caused by moving RBCs. Thus, the VCS signal can be assigned as a reference one with respect to more complicated signals like in laser Doppler flowmetry (LDF). An essential correlation between blood flow velocity oscillations in a separate human capillary and the integral perfusion estimate obtained by the LDF method has been found. The observation of blood flow by the VCS method during upper arm occlusion has shown emergence of the reverse blood flow effect in capillaries that corresponds to the biological zero signal in the LDF. The reverse blood flow effect has to be taken into account in interpretation of LDF signals. Abstract : The high‐speed videocapillaroscopy method provides unique information about the capillary net. This study empirically confirms the similarity between red blood cells velocity into capillaries and blood perfusion evaluated by the laser Doppler flowmetry (LDF) method, thus demonstrating the deep connection of the LDF signal origin with objective physical characteristics of the skin blood microflow.